Thermo-Environmental Performance of Four Different Shapes of Solar Greenhouse Dryer with Free Convection Operating Principle and No Load on Product - Edwin Villagran; Juan Camilo Henao-Rojas; German Franco (Fluids, 2021)
Solar drying using greenhouse dryers is a viable method from the technical, economic, and environmental perspectives, allowing the drying of agricultural products for conservation purposes in different regions of the world. In Colombia, the drying of aromatic plants such as mint (Mentha spicata) is usually done directly and in open fields, which exposes the product to contamination and loss of quality. Therefore, the objective of this research was to use a three-dimensional computational fluid dynamics (CFD-3D) model previously successfully validated and implemented in this work to study the performance of air flow patterns, temperature, and humidity inside four greenhouse-type dryers contemplated for a region with hot and humid climatic conditions. The results found allowed us to observe that the spatial distribution of temperature and relative humidity are related to the air flows generated inside each dryer, therefore, there were differences of up to 7.91 °C and 23.81% for the same evaluated scenario. The study also allowed us to conclude that the CFD methodology is an agile and precise tool that allows us to evaluate prototypes that have not been built to real scale, which allows us to generate useful information for decision-making regarding the best prototype to build under a specific climate condition.